PENGARUH PEMBELAJARAN DALAM JARINGAN MENGGUNAKAN MEDIA PEMBELAJARAN E-LEARNING TERHADAP MOTIVASI BELAJAR SISWA DI MI AL ISHLAH KOTA BANDUNG - Sonia, Gina Aria; Nasir, Tatang Muh; Permana, Hidayat Aji; Karlaely, Irma; Warman, Oman (Fakultas Agama Islam Universitas Ibn Khaldun Bogor, 2024)
The background of this research is to determine the effect of online learning using E-Learning learning media on students' learning motivation. Online learning was developed to support face-to-face learning, especially during the current COVID-19 (Coronavirus Disease-19) pandemic. This study aims to find out (1) the reality of online learning using E-Learning learning media in class VIII MI Al Ishlah Kota Bandung (2) the reality of learning motivation for class VIII students of MI Al Ishlah Kota Bandung and (3) the effect of online learning using media learning on the learning motivation of class VIII students of MI Al Ishlah Kota Bandung. This study uses a quantitative approach, with descriptive methods, correlational data types. Data collection techniques are carried out by observation, questionnaires, and documentation. In this study, 32 students were taken as samples from class VIII MI Al Ishlah Kota Bandung. Data analysis of these two variables was carried out using statistical methods which were divided into two approaches, namely partial analysis and correlation analysis. Based on the results of data processing, it can be concluded that (1) The reality of learning in the network using E-Learning learning media is in a positive category (score 4.03), (2) The reality of student learning motivation is in a good category (score 4.25), and (3 ) The relationship between learning in the network using E-Learning learning media with student motivation is (a) the correlation coefficient is 0.687 which is included in the strong category. (b) The hypothesis is accepted, because tcount is 2.7 smaller than ttable with (28.5) and (c) The degree of influence of variable X on variable Y is 48%TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//